UNCTAD peer review mechanism for competition law : 10 years of existence - A comparative analysis of the implementation of the Peer Review's recommendations across several assessed countries - de Fays, Marie-Marie (United Nations New YorkUS, 2015)
Covers six countries or regional organisations that participated in UNCTAD Voluntary Peer Review Mechanism between 2005 and 2009, and that were no thoroughly covered by a complementary report to this present one. Assesses and identifies the strengths, weaknesses and outcomes of the Peer Review Mechanism and the associated Peer Review Report.